Adaptasi MSDM Berbasis Kompetensi Terhadap Perkembangan Teknologi Digital: Analisis Literatur - Sri Wahyuni (Pelantar Press, 2025)
This study aims to examine how competency-based human resource management (HRM) systems adapt to digital technology advancements through a literature review. Digital transformation has fundamentally reshaped business structures and dynamics, requiring organizations to adjust their strategies to maintain competitiveness. This research employs a literature study methodology, analyzing articles, journals, and academic documents published between 2021 and 2025. The findings reveal that organizations face several challenges, including difficulties in identifying and developing relevant digital competencies and resistance to change among employees. Various adaptation strategies have been implemented, such as project-based training programs and the selection of employees with appropriate digital skills. The success of these strategies depends significantly on key factors, including top management support, active employee participation, and effective organizational communication. The study concludes by emphasizing the importance of a strategic and proactive approach in HRM policymaking to foster digital competencies and cultivate a more flexible and responsive organizational culture in the face of technological changes. This research provides valuable insights for HRM practitioners in navigating technological disruptions and market dynamics